Method for detecting migration dynamics of energetic material components

CN122961941APending Publication Date: 2026-10-23INST OF CHEM CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611262878.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]鉴于上述的分析,本发明实施例旨在提供一种含能材料组分迁移动力学检测方法,用以解决现有技术样品用量大、前处理流程复杂、数据误差大、迁移组分动态扩散过程表征精度不足、检测成本高的问题中的至少一个

Benefits of technology

1、本发明在样品处理环节直接对推进剂粘接体系试件进行超薄切片,整体前处理流程简单,省去繁杂的样品预处理步骤,可规避复杂前处理过程中易引入额外干扰变量所造成的检测偏差;同时所需样品用量更少,对不同材质粘接试件的样品有更好的普适性。本发明检测方式采用显微红外光谱检测,全程在室温条件下完成测试,无需施加高温环境,可大幅降低待测迁移组分受热分解的风险。借助红外光谱对推进剂、衬层、绝热层粘接体系微米尺度区域内各迁移组分特征官能团的吸收峰变化进行定向解析,能够屏蔽体系内其余各类添加剂带来的信号干扰,精准测算目标迁移组分的扩散深度。依托上述检测结果,本方法可应用于固体火箭发动机燃烧室界面粘接性能评定、配方快速筛选以及产品贮存寿命预测工作。除此之外,本检测方法样品用量小,操作简便易实施,数据误差小,检测所用耗材与仪器运行成本相对低廉。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The present application relates to a kind of energetic material component migration dynamics detection method, belong to energetic material analysis technical field, solve the problems such as large sample consumption, complicated pretreatment, large data processing error and high detection cost in prior art.The method comprises the following steps:one, sample preparation and equipment selection;Two, implement spectrum detection, mark coordinate;Three, establish empirical formula, complete performance evaluation.The kinetics detection of various migration components in the bonding system of energetic material is realized.The technical scheme of the present application can effectively reduce the sample processing risk, simplify the sample pretreatment process, reduce the sample consumption, and the detection method is simple, the data repeatability is good, and is suitable for the detection of migration components in different compositions and different types of energetic materials, and can be used for evaluating bonding quality, rapid formula screening and aging monitoring, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energetic materials analysis technology, and in particular to a method for detecting the migration kinetics of energetic materials components. Background Technology

[0002] Energetic material bonding systems are widely used in aerospace, missile, and solid rocket engine fields. They are multi-layered heterogeneous composite interface systems consisting of propellant grains, liners, and insulation layers. The system uses polymer materials as the bonding matrix, combined with energetic plasticizers, solid fillers, curing agents, and various functional additives. The liner facilitates the transition between the propellant grains and the insulation layer. This system achieves reliable bonding of multi-layered structures, coordinates the mechanical properties of each layer, alleviates interfacial stresses caused by temperature cycling and vibration loads, and relies on the insulation layer to block high-temperature combustion gases, preventing the shell from being ablated by high temperatures and ensuring the overall structural integrity of the propellant. The system has stringent requirements for interfacial bonding strength, component compatibility, and long-term chemical stability. Migration of components such as small-molecule plasticizers in the propellant can alter the component distribution of each layer, affect the interfacial bonding performance, shorten the storage life of the propellant, and pose safety risks.

[0003] In existing technologies, chromatography, including gas chromatography and high-performance liquid chromatography (HPLC), is widely used for detecting migrating components in the bonding systems of energetic materials such as solid rocket fuel in aerospace and missile technology, simultaneously determining the main migrating components in the system. However, chromatography has certain drawbacks in determining migrating components in nitrate ester plasticized polyether propellant / liner / insulation layer systems: First, chromatography requires a large sample volume. Following standard chromatographic procedures, a single determination requires several grams or even tens of grams of sample from each layer of the bonding system, which is often insufficient for small-sized specimens. Second, the sample pretreatment process for the bonding system in chromatography is complex, requiring manual stripping of each bonding layer, solvent extraction, purification, and concentration, which can easily lead to cross-contamination between different bonding layers. Third, the sources of error in the experimental data obtained by chromatography are complex, such as inconsistent solvent extraction efficiency, decomposition of migrating components due to high temperatures at the gas chromatographic inlet, and matrix effects caused by co-eluting peaks from other additives and impurities in the sample. Furthermore, chromatographic detection is costly, encompassing the costs of consumables such as chromatographic solvents and columns, as well as instrument maintenance. In addition, chromatography is a destructive sampling method, making it difficult to track the dynamic diffusion behavior of migrating components in situ. Furthermore, the use of large amounts of extraction solvents also brings additional safety and environmental burdens, failing to meet the actual need for non-destructive and rapid monitoring of the interface failure process of this type of energetic adhesive system.

[0004] Currently, the most common method for detecting component migration in adhesive systems is multi-time-point aging combined with chromatographic quantitative testing. This involves preparing multiple identical adhesive specimens, conducting accelerated aging tests for different durations, and extracting the corresponding specimens at each preset time point. Then, the aforementioned chromatographic method is used for stratified sampling to determine the content of migrating components. Kinetic parameters such as diffusion coefficients are obtained by fitting the concentration data from multiple discrete time points. While this method can initially obtain component migration kinetic data, it has certain drawbacks: First, the experiment requires a large number of parallel adhesive specimens, and differences in specimen preparation can introduce errors in kinetic fitting. Second, the destructive sampling chromatographic method only yields data for a single aging time for the same specimen, failing to capture component migration within the same sample. Furthermore, stratified stripping sampling destroys the original interface structure of the specimen, making it impossible to obtain in-situ component concentration gradients in the interface region, thus hindering accurate characterization of component diffusion behavior at the interface. In addition, migration kinetic auxiliary characterization methods such as gravimetric methods and single-spectral offline testing also generally suffer from insufficient quantitative accuracy, difficulty in distinguishing multiple migrating components, and inability to obtain local concentration distributions at the interface. Summary of the Invention

[0005] Based on the above analysis, the present invention aims to provide a method for detecting the migration kinetics of energetic material components, in order to solve at least one of the problems of existing technologies, such as large sample volume, complex pretreatment process, large data error, insufficient accuracy in characterizing the dynamic diffusion process of migrating components, and high detection cost.

[0006] This invention discloses a method for detecting the migration kinetics of energetic materials, the steps of which include: S1. Sample preparation: The energetic material bonding system specimen was ultra-thinly sectioned under liquid nitrogen freezing environment; S2. Spectral detection: Microscopic infrared spectroscopy detection is performed along the normal direction of the slice interface, with a detection area interval of 10-50 μm; the interface position coordinates are determined based on the microscopic imaging, and the diffusion depth dx of the migrating component is determined in combination with the detection area interval; S3. Establish empirical relationship: Collect infrared spectral data of slices at different diffusion depths, preprocess the infrared spectral data, and fit the peak area of ​​the absorption peak of a specific group based on the preprocessed data to obtain the relative concentration dC of the migrating component, and establish an empirical relationship between the diffusion depth dx of the migrating component and the relative concentration dC.

[0007] Furthermore, the slice thickness in step S1 is 1~8 μm.

[0008] Furthermore, the micro-infrared spectroscopy detection in step S2 is performed using a Fourier transform micro-infrared spectrometer.

[0009] Furthermore, the energetic material bonding system includes a propellant, a liner, and an insulation layer, and in step S2, the position coordinates of the physical interface between the propellant and the liner or the liner and the insulation layer are defined as 0.

[0010] Furthermore, the processing of infrared spectral data in step S3 includes baseline correction and smoothing.

[0011] Further, the specific group absorption peak mentioned in step S3 is the characteristic absorption peak of the -NO2 group and the characteristic absorption peak of the -CH2 group in the nitrate ester; wherein, the characteristic absorption peak of the -CH2 group is used as an internal reference peak.

[0012] Further, the relative concentration dC mentioned in step S3 is calculated by the ratio of the characteristic absorption peak area of ​​the -NO2 group in the nitrate ester to the characteristic absorption peak area of ​​the -CH2 group in the internal reference peak.

[0013] Furthermore, the detection method also includes determining the content of the migrating component based on the characteristic absorption peak area of ​​the specific group corresponding to the migrating component and the characteristic absorption peak area of ​​the internal reference peak.

[0014] Furthermore, the content of the migrating component is calculated as follows: the ratio of the characteristic absorption peak area of ​​the migrating component to the characteristic absorption peak area of ​​the internal reference peak is selected to obtain the relative concentration of the migrating component, and the relative concentration is used to characterize the content of the migrating component.

[0015] Furthermore, the method is used for evaluating the adhesion performance of solid rocket motor combustion chamber interfaces, rapid formula screening, and storage life prediction.

[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. This invention directly performs ultrathin sectioning on the propellant bonding system specimens during sample processing, simplifying the overall pretreatment process and eliminating complex sample pretreatment steps. This avoids detection deviations caused by additional interference variables introduced during complex pretreatment processes. Simultaneously, it requires less sample and has better universality for samples with different bonding materials. The detection method of this invention employs microscopic infrared spectroscopy, completing the entire test at room temperature, eliminating the need for a high-temperature environment and significantly reducing the risk of thermal decomposition of the target migrating components. By using infrared spectroscopy to directionally analyze the absorption peak changes of characteristic functional groups of each migrating component in the micron-scale region of the propellant, liner, and insulation layer bonding system, it can shield the signal interference from other additives in the system and accurately calculate the diffusion depth of the target migrating component. Based on the above detection results, this method can be applied to the evaluation of the interface bonding performance of solid rocket engine combustion chambers, rapid formulation screening, and product storage life prediction. Furthermore, this detection method requires a small sample volume, is simple to operate and implement, has small data errors, and the operating costs of consumables and instruments used in the detection are relatively low.

[0017] 2. This invention employs ultrathin slicing combined with microscopic infrared characterization, belonging to non-destructive in-situ detection technology. Traditional detection methods require damaging the specimen structure for layered sampling, making long-term continuous tracking of the same specimen impossible. This invention, however, can achieve in-situ detection of the micron-level region of the bonding interface without damaging the original interface structure of the adhesive system or the overall morphology of the specimen. It preserves the complete interlayer structural characteristics of the specimen, enabling the reconstruction of the entire dynamic diffusion process of migrating components over time and the changing characteristics of component migration. This provides real and complete in-situ data support for analyzing the interface failure evolution mechanism of the adhesive system.

[0018] 3. Compared to existing technologies that can only detect the overall average component content of the test specimen and only fit macroscopic kinetic parameters, this invention can achieve fine detection of the bonding interface at micron-level resolution. It can simultaneously acquire multi-dimensional and rich dynamic data such as the diffusion depth of migrating components, the relative content of components at various locations on the interface, and the distribution of component concentration gradients. Traditional discrete sampling detection methods can only obtain overall average data at a single time point, which cannot reflect the differences in component migration at the interface. However, this invention can accurately characterize the continuous component concentration distribution pattern at the bonding interface from the propellant layer, transition liner to the insulation layer, clearly locate the component diffusion front, quantify the degree of component migration at different aging stages, greatly enrich the data dimensions of migration kinetics research, and more accurately fit kinetic parameters such as diffusion coefficients.

[0019] 4. This invention eliminates the cumbersome experimental procedures of complex sample pretreatment and multiple rounds of chromatographic detection required by existing kinetic detection methods. Furthermore, the detection process does not require large amounts of chromatographic-grade organic solvents, chromatographic columns, or other consumables, and there are no complex sample pretreatment and purification / concentration steps. The experimental procedure is extremely simple, and the detection cycle is significantly shortened, enabling rapid batch detection of the migration behavior of components in adhesive systems. Compared to the drawbacks of traditional detection methods, such as high labor costs, high consumable consumption, and high instrument maintenance costs, this invention improves detection efficiency and reduces the costs of detection consumables, time, and equipment operation and maintenance.

[0020] 5. The technical solution of this invention can be used to conduct long-term tracking of the same specimen (or parallel specimens in the same batch), characterize the dynamic diffusion process of migrating components, and truly restore the dynamic evolution process of component migration. This solves the problems of insufficient quantitative accuracy, large fitting error, and inability to obtain the local concentration distribution at the interface in existing adhesive system migration component kinetic detection methods.

[0021] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objectives and other advantages of this invention can be realized and obtained through the specific points highlighted in the description. Detailed Implementation

[0022] Energetic material bonding systems are widely used in aerospace, missile, and solid rocket motor fields. These systems have stringent requirements for interfacial bond strength, component compatibility, and long-term chemical stability. Existing methods for detecting component migration kinetics involve timed aging of multiple parallel specimens combined with offline chromatography. This method requires the preparation of a large number of parallel bonded specimens, destructive sampling of the specimens in batches at different aging points, and fitting of kinetic parameters based on the average content data at discrete time points. This is an offline, averaging detection method, where only the overall average component information at a single moment can be obtained for a single specimen. The large number of parallel specimens required and the risks of cross-contamination and component decomposition introduced by pretreatment methods such as manual peeling and solvent extraction are also significant concerns.

[0023] This invention employs ultrathin slicing combined with in-situ micro-infrared micro-region characterization. The original structural information of the bonding interface can be preserved simply by slicing, and the detection can be completed at room temperature, avoiding thermal decomposition of migrating components. It can directly obtain the continuous component concentration gradient and diffusion front position at the micrometer scale perpendicular to the interface direction, providing richer data dimensions and more realistically reflecting the migration and evolution of cross-interface components.

[0024] The purpose of this invention is to provide a method for detecting the migration kinetics of energetic material components. This method is applicable to different types of energetic material bonding systems, especially nitrate ester plasticized polyether propellant / liner / insulation layer systems. It can effectively reduce sample volume, simplify sample pretreatment procedures, reduce data processing errors, and save detection costs.

[0025] The preferred embodiments of the present invention are described in detail below. These embodiments are used to illustrate the principles of the present invention and are not intended to limit the scope of the present invention.

[0026] A specific embodiment of the present invention discloses a method for detecting the migration kinetics of energetic material components, the steps of which include: S1. Sample preparation: The energetic material bonding system specimen was ultra-thinly sectioned under liquid nitrogen freezing environment; S2. Spectral detection: Microscopic infrared spectroscopy detection is performed along the normal direction of the slice interface, with a detection area interval of 10-50 μm; the interface position coordinates are determined based on the microscopic imaging, and the diffusion depth dx of the migrating component is determined in combination with the detection area interval; S3. Establish empirical relationship: Collect infrared spectral data of slices at different diffusion depths, preprocess the infrared spectral data, and fit the peak area of ​​the absorption peak of a specific group based on the preprocessed data to obtain the relative concentration dC of the migrating component, and establish an empirical relationship between the diffusion depth dx of the migrating component and the relative concentration dC.

[0027] Compared with existing technologies, the sample pretreatment technique used in this invention can largely avoid the destructive sampling of specimens in traditional chromatographic tests. Furthermore, the low-temperature freezing environment can slow down the decomposition of migrating components such as nitrate esters. In addition, compared with common kinetic testing methods that can only test the overall content of migrating components in a specimen at a specific aging time point, microscopic infrared spectroscopy can test different migration depths after imaging the slices, enabling micron-level characterization of component migration in a specimen and directly obtaining the migration depth and relative concentration of components near the interface. This detection method is simple to operate and implement, has excellent repeatability of detection data, accurate and stable data analysis results, and relatively low consumable and instrument operating costs.

[0028] Specifically, the preparation of the energetic material bonding system specimen in step S1 includes the following steps: First, a heat insulation layer substrate is prepared by molding, and a primer is applied to the bonding surface of the heat insulation layer and allowed to dry. Next, a liner slurry is prepared, uniformly coated on the surface of the heat insulation layer, and pre-cured. Subsequently, a propellant slurry is prepared, degassed under vacuum, and poured onto the liner. Finally, after the assembled laminated specimen has cured, it is cut and trimmed to obtain the energetic material bonding system specimen.

[0029] Specifically, in step S1, the energetic material bonding system specimen is subjected to ultrathin sectioning under liquid nitrogen freezing conditions. The section thickness is 1~8μm, such as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, and 8μm. If the section thickness exceeds 8μm, insufficient light transmittance will result in quantitative distortion of infrared absorbance due to excessive thickness; when the thickness is less than 1μm, the section is easily damaged and wrinkled, making it difficult to obtain a complete section. This invention controls the section thickness to 1~8μm, which can balance the infrared spectral transmittance and sample structural integrity, and suppress light scattering interference.

[0030] Specifically, in step S2, microscopic infrared spectroscopy is performed along the interface normal direction. The detection area interval is 10–50 μm; the interface position coordinates are determined based on the microscopic imaging, and the diffusion depth dx of the migrating component is determined in combination with the detection area interval.

[0031] Specifically, the micro-infrared spectroscopy detection employs a Fourier transform infrared microscopy (FTIR) spectrometer. FTIR spectrometers possess both qualitative identification capabilities for organic components and micrometer-level spatial resolution. They can perform in-situ micro-area testing at room temperature, avoiding the risk of high-temperature decomposition of nitrate ester components. Furthermore, they can visualize the morphology of slices and identify interface locations through microscopic imaging, and support linear continuous scanning along the perpendicular bonding interface to obtain continuous distribution data of component concentrations across layers, supporting the analysis of component migration kinetics.

[0032] For example, the detection zone interval can be 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, or 50μm, preferably 25μm. The detection zone interval determines the sampling density of component distribution, and the selection is based on factors including the expected component diffusion distance, the required spatial resolution, and the detection time. An interval that is too large will result in the loss of key concentration change information, while an interval that is too small will significantly increase the testing time. A range of 10–50μm can balance detection resolution and testing efficiency, fully capture the evolution of component concentration gradients at the adhesive interface, and effectively control the detection time.

[0033] Specifically, the energetic material bonding system includes a propellant, a liner, and an insulation layer. In step S2, the position coordinates of the physical interface between the propellant and the liner or the liner and the insulation layer are defined as 0. Defining the interface position coordinates as 0 provides a unified reference benchmark for calculating component migration kinetics, adapts to the fitting of migration component kinetic models, and allows for segmented analysis of migration behavior between adjacent layers, making the visualization and pattern analysis of concentration distribution data more intuitive.

[0034] The physical interface coordinates of the liner / insulation layer are defined as 0. Microscopic infrared spectra at different positions in the normal direction are collected sequentially according to the set detection interval. Based on the slice image during microscopic infrared spectroscopy detection, the interface position and the diffusion layer coordinates of each detection point are determined simultaneously, and finally the diffusion depth dx of the migrating component is accurately obtained.

[0035] Specifically, the interface coordinates are determined by microscopic imaging. Microscopic imaging of ultrathin sections using a micro-infrared spectroscopy instrument allows for clear observation of the physical interface positions of the propellant / liner / insulation layer. The diffusion depth dx of the migrating component is then determined by combining this with the detection area interval. Using the selected interface as the origin, along the direction perpendicular to the interface normal, and considering the detection area interval, the diffusion depth of the migrating component can be determined. For example, when the detection area interval is 25 μm, the diffusion depth dx of the first detection point from the origin is 25 μm, and the diffusion depth dx of the second detection point is 50 μm.

[0036] Specifically, in step S3, infrared spectral data at different diffusion depths of the slice are collected, preprocessed, and the peak areas of specific group absorption peaks are fitted based on the preprocessed data to obtain the relative concentration dC of the migrating component. An empirical relationship (i.e., migration kinetic curve) between the diffusion depth dx and the relative concentration dC of the migrating component is established to accurately characterize the migration behavior of nitrate esters. The specific group absorption peak is the characteristic absorption peak of interest, and peak fitting is performed on the infrared spectral data within the wavenumber range of the characteristic absorption peak of interest.

[0037] Specifically, step S3, the preprocessing of the infrared spectral data, includes baseline correction and smoothing. Baseline correction corrects baseline tilt caused by sample scattering and instrument background drift, unifying the absorbance calculation benchmark; smoothing filters out random noise, eliminates spectral glitches, and improves the spectral signal-to-noise ratio. Through these preprocessing steps, accurate identification of characteristic peaks is ensured, and the stability of peak area quantification results is improved.

[0038] Specifically, in step S3, the migrating component of interest in the ultrathin micro-infrared spectra at different locations in the collected insulation layer slices is nitrate ester. The selected specific groups and their characteristic absorption peaks include: 1649 cm⁻¹ -1 The characteristic absorption peak of the nitrate ester -NO2 group at 1460 cm⁻¹ -1 The absorption peak at the -CH2 position; that is, the absorption peak of the specific group is the characteristic absorption peak of the -NO2 group and the characteristic absorption peak of the -CH2 group in the nitrate ester; wherein, the characteristic absorption peak of the -CH2 group is used as an internal reference peak. The -NO2 group is a specific functional group of the migrating component nitrate ester, and its characteristic absorption peak is used to characterize the relative content of the migrating component; -CH2 is universally present in the polymer backbone of each layer system, its chemical properties are stable and its content is basically constant. Using its characteristic absorption peak as an internal reference peak can effectively correct systematic errors caused by uneven slice thickness and optical path fluctuations. At the same time, the peak positions of the two characteristic peaks do not overlap, which can avoid mutual interference of spectral peaks and ensure detection accuracy. It should be noted that the peak positions of the characteristic absorption peak of the -NO2 group and the -CH2 absorption peak of the nitrate ester may vary slightly when using different micro-infrared spectrometers.

[0039] Specifically, the relative concentration dC mentioned in step S3 is calculated by the ratio of the characteristic absorption peak area of ​​the -NO2 group in the nitrate ester to the characteristic absorption peak area of ​​the -CH2 group in the internal reference peak. Based on the diffusion depth dx and the relative concentration dC, an empirical relationship between the diffusion depth and relative concentration of the migrating component is established, allowing for the acquisition of component migration depth information accurate to the micrometer level.

[0040] In infrared spectroscopy, uneven slice thickness, differences in surface flatness, or fluctuations in the optical path can all lead to overall changes in absorbance (or reflectance). An internal reference peak (such as the -CH2 group in this example, 1460 cm⁻¹) is selected by choosing a chemical group with a constant content in the matrix that does not change with migration. -1 Calculating the ratio of the target peak area to the internal reference peak area can eliminate systematic errors caused by the aforementioned physical factors. This is a prerequisite step and the basis for calculating the "relative concentration dC".

[0041] Compared to existing technologies, this invention uses internal reference normalization to calculate relative concentrations and perform modeling, which can eliminate detection errors caused by differences in slice thickness and optical path fluctuations, and improve the stability of fitting results. Based on the micron-level measured diffusion depth, the relationship can accurately reflect the concentration distribution variation law of the migrating components. At the same time, this method can perform segmented migration analysis on multilayer adhesive structures and has better applicability to different adhesive systems.

[0042] Specifically, the detection method further includes determining the content of the migrating component based on the characteristic absorption peak area of ​​the specific group corresponding to the migrating component and the characteristic absorption peak area of ​​the internal reference peak.

[0043] Specifically, the method for calculating the content of the migrating component is as follows: the ratio of the characteristic absorption peak area of ​​the migrating component to the characteristic absorption peak area of ​​the internal reference peak is used to calculate the relative concentration of the migrating component, and the relative concentration is used to characterize the content of the migrating component.

[0044] Specifically, the energetic material component migration kinetics detection method of this invention is applicable to the evaluation of adhesive performance, rapid formulation screening, and storage life prediction of solid rocket engine combustion chamber interfaces. By preparing composite interface samples of propellant and insulation or lining layers, accelerated aging experiments are conducted under simulated service environment temperature and humidity conditions. Combining the concentration gradient and migration depth of migrating components with mechanical test results, a correlation model between the distribution characteristics of migrating components and adhesive mechanical properties is established, thereby achieving accurate evaluation of interface adhesive performance. Furthermore, for multiple candidate formulations, the method of this invention can quickly obtain the diffusion of migrating components in specimens with different formulations within the same batch, enabling rapid screening of anti-migration formulations. In addition, regarding storage life prediction, by conducting isothermal accelerated aging experiments at multiple different temperature gradients, a component migration kinetics model is established. By fitting the quantitative relationship between temperature and migration rate constant, the storage life under actual conditions can be extrapolated and predicted.

[0045] It should be noted that the accurate detection of component migration in multilayer adhesive systems of energetic materials faces numerous inherent technical barriers due to the system's structure and detection characteristics. This invention addresses these challenges one by one through targeted process and detection method optimization: First, the propellant, liner, and insulation layer constitute a multilayer heterogeneous polymer system with both soft and hard components. Conventional slicing easily causes interlayer tearing and interface misalignment, damaging the true migration interface. This invention employs a low-temperature cryogenic continuous ultrathin slicing process, ensuring the complete preservation of the multilayer adhesive interface through matched freezing temperature and slice thickness. Second, the infrared absorption peaks of the polymer matrix and various functional additives in the system overlap, easily masking the characteristic signal of the target nitrate ester component. This invention specifically selects the absorption peaks of nitrate ester-specific characteristic functional groups for analysis, combined with spectral baseline subtraction, to eliminate spectral interference from the matrix and impurities. Third, single-point testing only obtains discrete data, making it difficult to construct continuous concentration distribution curves to support kinetic modeling. This invention uses micro-infrared technology to perform linear continuous scanning along the vertical adhesive interface, comprehensively acquiring continuous spectral information of micro-regions along the component diffusion path. Fourth, fluctuations in slice thickness and uneven distribution of solid fillers can easily lead to deviations in infrared quantitative results. This invention introduces an internal standard normalization quantitative strategy, using the characteristic peaks of stable components in the system to correct absorbance, significantly improving the accuracy of component quantification and ensuring the reliability of kinetic parameter fitting.

[0046] To more clearly describe the present invention, the following embodiments and comparative examples are provided for further illustration. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0047] Example 1 In Example 1, a typical bonding system of energetic materials—NEPE propellant / HTPB liner / EPDM insulation layer bonding specimen—was selected and aged at 60°C for 192 days to determine the migration of nitrate ester components in the insulation layer.

[0048] The preparation process of the energetic material bonding system specimen is as follows: First, EPDM (ethylene propylene diene monomer) rubber insulation layer substrate is prepared by molding. A primer is applied to the bonding surface of the insulation layer and allowed to dry. Next, hydroxyl-terminated polybutadiene (HTPB) liner slurry is prepared, uniformly coated on the surface of the insulation layer, and pre-cured. Then, nitrate ester plasticized polyether (NEPE) propellant slurry is prepared, degassed under vacuum, and poured onto the liner. After the assembled laminated specimen is cured, the interfaces of each layer are ensured to be firmly bonded. After curing, it is cut and trimmed to obtain the NEPE propellant / HTPB liner / EPDM insulation layer bonding specimen.

[0049] Step 1: Considering experimental safety, the nitrate ester plasticized polyether (NEPE) propellant layer, the hydroxyl-terminated polybutadiene (HTPB) liner, and the ethylene propylene diene monomer (EPDM) insulation layer were peeled off along the interface. The hydroxyl-terminated polybutadiene (HTPB) liner was processed into a sample with the required size and thickness to fit the cryostat. Using a cryostat under liquid nitrogen freezing conditions, an ultrathin section of the insulation layer with a thickness of 6 μm along the interface normal was cut. The section was then laid flat on the surface of a gold mirror for subsequent spectral detection.

[0050] Step two: Micro-infrared spectroscopy is performed using a Fourier transform micro-infrared spectrometer. Detection points are arranged along the interface normal direction with an interval of 25 μm. The interval can be adjusted appropriately according to the signal intensity. The position coordinates of the physical interface of the liner / insulation layer are defined as 0. Micro-infrared spectra at different positions along the normal direction are collected sequentially according to the set detection interval. Based on the slice image during micro-infrared spectroscopy detection, the interface position and the diffusion layer coordinates of each detection point are determined simultaneously. Finally, the diffusion depth dx of the migrating component is accurately obtained.

[0051] Step 3: Baseline correction and smoothing are performed on the infrared spectral data at different diffusion depths of the slices. Peak fitting is then performed on the infrared spectral data within the wavenumber range of the characteristic absorption peaks of interest to obtain the peak areas of the characteristic absorption peaks. In the micro-infrared spectra at different locations in the collected ultrathin insulating layer slices, the migrating component of interest is nitrate ester. The selected specific groups and their characteristic absorption peaks include: 1649 cm⁻¹. -1 The characteristic absorption peak of the nitrate ester -NO2 group at 1460 cm⁻¹ -1 The -CH2 absorption peak is located at 1460 cm⁻¹; among which, the peak at 1460 cm⁻¹ is the highest. -1 The -CH2 absorption peak at the point is used as an internal reference peak for the insulation layer. The relative concentration dC of the migrating component is calculated by the ratio of the characteristic absorption peak area A-NO2 of the -NO2 group in the nitrate ester to the characteristic absorption peak area A-CH2 of the -CH2 group in the internal reference peak. A data table of diffusion depth dx and relative concentration dC of the migrating component at the insulation layer interface after 60℃ aging for 192 days is formed, as shown in Table 1. An empirical formula for component migration is then established. Furthermore, based on the test results, migration depths accurate to the micrometer level can be obtained.

[0052] Table 1. Data on the diffusion depth dx, -NO2 peak area A-NO2, internal reference peak area A-CH2, and relative concentration dC of the migrating component nitrate ester in Example 1.

[0053] Table 1 shows that in the shallow region (0–800 μm) of the insulation layer, the diffusion depth dx and the relative concentration dC of the migrating component nitrate ester are highly negatively correlated; that is, the relative concentration of nitrate ester decreases linearly with increasing diffusion depth. Beyond 800 μm, the relative concentration no longer changes. For this embodiment, the empirical relationship between the diffusion depth dx and the relative concentration dC of the migrating component nitrate ester in the shallow region of the insulation layer is as follows: dC= 0.00036 dx+0.58658(1) Based on the infrared spectroscopy test results, the migration depth of the nitrate ester component under the interface of the insulation layer aged at 60℃ for 192 days was found to be 800 μm.

[0054] Example 2 The preparation method of the energetic material bonding specimen in Example 2 is largely the same as that in Example 1, except that the material of the HTPB liner is different. In this example, no other additives such as functional auxiliaries were added to the HTPB liner material. The NEPE propellant / HTPB liner / EPDM insulation bonding specimen was aged at 50°C for 21 days, and the migration of nitrate ester components in the liner without additives was measured.

[0055] Step 1: Considering experimental safety, the nitrate ester plasticized polyether (NEPE) propellant layer, the hydroxyl-terminated polybutadiene (HTPB) liner, and the ethylene propylene diene monomer (EPDM) insulation layer were peeled off along the interface. The hydroxyl-terminated polybutadiene (HTPB) liner was processed into a sample with the required size and thickness to fit the cryostat. Using a cryostat under liquid nitrogen freezing conditions, an ultrathin section of the insulation layer with a thickness of 6 μm along the interface normal was cut. The section was then laid flat on the surface of a gold mirror for subsequent spectral detection.

[0056] Step two: Micro-infrared spectroscopy is performed using a Fourier transform micro-infrared spectrometer. Detection points are arranged along the interface normal direction with an interval of 25 μm. The interval can be adjusted appropriately according to the signal intensity. The position coordinates of the physical interface of the propellant / liner are defined as 0. Micro-infrared spectra at different positions along the normal direction are collected sequentially according to the set detection interval. Based on the slice images during micro-infrared spectroscopy detection, the interface position and the diffusion layer coordinates of each detection point are determined simultaneously, and the diffusion depth dx of the migrating component is finally accurately obtained.

[0057] Step 3: Baseline correction and smoothing are performed on the infrared spectral data at different diffusion depths of the slices. Peak fitting is then performed on the infrared spectral data within the wavenumber range of the characteristic absorption peaks of interest to obtain the peak areas of the characteristic absorption peaks. In the micro-infrared spectra at different locations in the collected ultrathin insulating layer slices, the migrating component of interest is nitrate ester. The selected specific groups and their characteristic absorption peaks include: 1649 cm⁻¹.-1 The characteristic absorption peak of the nitrate ester -NO2 group at 1446 cm⁻¹ -1 The -CH2 absorption peak is located at 1446 cm⁻¹; among them, the peak value is 144 -1 The -CH2 absorption peak at the point is used as an internal reference peak for the insulation layer. The relative concentration dC of the migrating component is calculated by the ratio of the characteristic absorption peak area A-NO2 of the -NO2 group in the nitrate ester to the characteristic absorption peak area A-CH2 of the -CH2 group in the internal reference peak. A data table of diffusion depth dx and relative concentration dC of the migrating component at the insulation layer interface after 50℃ aging for 21 days is formed, as shown in Table 2. An empirical formula for component migration is then established. Furthermore, based on the test results, migration depths accurate to the micrometer level can be obtained.

[0058] Table 2. Data on the diffusion depth dx, -NO2 peak area A-NO2, internal reference peak area A-CH2, and relative concentration dC of the migrating component nitrate ester in Example 2.

[0059] Table 2 shows that in the shallow region (0–525 μm) of the liner, the diffusion depth dx and the relative concentration dC of the migrating nitrate component exhibit a strong negative correlation; that is, the relative concentration of nitrate decreases linearly with increasing diffusion depth. Beyond 525 μm, the relative concentration no longer changes. For this embodiment, the empirical relationship between the diffusion depth dx and the relative concentration dC of the migrating nitrate component in the shallow region of the liner is as follows: dC= 0.00061 dx+0.94225(2) Based on the infrared spectroscopy test results, the migration depth of the nitrate ester component under the liner interface after aging at 50℃ for 21 days was found to be 525 μm.

[0060] Example 3 The preparation method of the energetic material bonding specimen and the determination method of the migration of the nitrate ester component in the liner in this embodiment are largely the same as those in Example 2. The only difference is that the NEPE propellant / HTPB liner / EPDM insulation layer bonding specimen is aged at 50°C for 48 days.

[0061] Table 3 is a list of data on the diffusion depth dx, the -NO2 peak area A-NO2 in the nitrate ester, the internal reference peak area A-CH2, and the relative concentration dC of the migrating component nitrate ester in this embodiment.

[0062] Table 3. Data on the diffusion depth dx, -NO2 peak area A-NO2, internal reference peak area A-CH2, and relative concentration dC of the migrating component nitrate ester in Example 3.

[0063] Table 3 shows that in the shallow region (0–650 μm) of the liner, the diffusion depth dx and the relative concentration dC of the migrating nitrate component exhibit a strong negative correlation; that is, the relative concentration of nitrate decreases linearly with increasing diffusion depth. Beyond 650 μm, the relative concentration no longer changes. For this embodiment, the empirical relationship between the diffusion depth dx and the relative concentration dC of the migrating nitrate component in the shallow region of the liner is: dC= 0.00057 dx + 0.73085 (3) Based on the infrared spectroscopy test results, the migration depth of the nitrate ester component under the liner interface after aging at 50℃ for 48 days was found to be 650 μm.

[0064] In the above embodiments, the data were all measured repeatedly, and the results showed that the repeatability of the data was good.

[0065] In the detection of migrating components in energetic material bonding systems, existing technologies mostly employ chromatography. However, chromatography requires large sample volumes, involves complex sample preparation processes, has complex sources of error in experimental data, and is costly. Furthermore, it is a destructive sampling method, where a single sample can only be detected once, and only the average value at a certain moment can be obtained. It is impossible to know the spatial distribution, make it difficult to track the dynamic diffusion behavior of migrating components in situ, and also make it impossible to track the evolution of component migration over time in the same specimen.

[0066] In this embodiment of the invention, ultrathin cryosections are taken from the energetic material bonding system specimens, resulting in a small sample volume. Then, microscopic infrared spectroscopy is used for detection; this is an in-situ, non-destructive detection method. After detection, the data are normalized to internal reference peaks, with 1460 cm⁻¹ selected as the peak value. -1 The -CH2 group at the sample site is used as an internal reference peak. Since the content of the -CH2 group in the matrix is ​​constant, the relative concentration (dC) is characterized by calculating the peak area ratio of the nitrate ester characteristic peak (-NO2) to the internal reference peak (-CH2), effectively eliminating systematic errors caused by slight differences in slice thickness, optical path fluctuations, or sample surface unevenness. This in-situ, non-destructive detection method avoids sample loss and contamination during chromatographic extraction, reducing data processing errors at the source.

[0067] In embodiments 1, 2, and 3 of this invention, data is collected every 25 μm along the interface normal direction. This results in denser data points, more clearly reflecting concentration abrupt changes at the interface. By constructing continuous concentration gradient curves, the dynamic distribution profile of the migrating component diffusing from the interface to the interior is displayed, rather than a single average value. Chromatography, due to limitations in peel thickness, cannot capture such fine interfacial changes.

[0068] In Example 2, the nitrate ester migration depth of the bonded specimen after aging at 50°C for 21 days was 525 μm; in Example 3, the nitrate ester migration depth of the bonded specimen after aging at 50°C for 48 days was 650 μm. Comparing Examples 2 and 3 shows that as the aging time increases, the nitrate ester migration depth in the bonded specimen increases, and the component concentration gradient changes accordingly. This indicates that the technical solution of this invention can be used to conduct long-term tracking of the same specimen (or parallel specimens from the same batch), characterizing the dynamic diffusion process of migrating components and accurately and realistically reproducing the dynamic evolution of component migration. Existing chromatographic methods lack the ability to characterize the dynamic diffusion process of migrating components in the same specimen.

[0069] The above embodiments demonstrate that the energetic material component migration kinetics detection method provided by the present invention requires a small sample volume, is simple to operate and implement, has small data errors, and has relatively low operating costs for consumables and instruments. It is applicable to energetic material bonding systems with different materials and different aging times, and can obtain the entire dynamic diffusion process of migrating components and the change characteristics of component migration in the bonding system.

[0070] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for detecting the migration kinetics of energetic material components, characterized in that, The detection method includes the following steps: S1. Sample preparation: The energetic material bonding system specimen was ultra-thinly sectioned under liquid nitrogen freezing environment; S2. Spectral detection: Microscopic infrared spectroscopy detection is performed along the normal direction of the slice interface, with a detection area interval of 10-50 μm; the interface position coordinates are determined based on the microscopic imaging, and the diffusion depth dx of the migrating component is determined in combination with the detection area interval; S3. Establish empirical relationship: Collect infrared spectral data of slices at different diffusion depths, preprocess the infrared spectral data, and fit the peak area of ​​the absorption peak of a specific group based on the preprocessed data to obtain the relative concentration dC of the migrating component, and establish an empirical relationship between the diffusion depth dx of the migrating component and the relative concentration dC.

2. The method for detecting the migration kinetics of energetic material components according to claim 1, characterized in that, The thickness of the slice in step S1 is 1~8μm.

3. The method for detecting the migration kinetics of energetic material components according to claim 1, characterized in that, The micro-infrared spectroscopy detection in step S2 uses a Fourier transform micro-infrared spectrometer.

4. The method for detecting the migration kinetics of energetic material components according to claim 1, characterized in that, The energetic material bonding system includes a propellant, a liner, and an insulation layer. In step S2, the position coordinates of the physical interface between the propellant and the liner or the liner and the insulation layer are defined as 0.

5. The method for detecting the migration kinetics of energetic material components according to claim 1, characterized in that, The preprocessing of infrared spectral data in step S3 includes baseline correction and smoothing.

6. The method for detecting the migration kinetics of energetic material components according to claim 1, characterized in that, The specific absorption peaks mentioned in step S3 are the characteristic absorption peaks of the -NO2 group and the -CH2 group in nitrate esters; wherein, the characteristic absorption peak of the -CH2 group is used as an internal reference peak.

7. The method for detecting the migration kinetics of energetic material components according to claim 6, characterized in that, The relative concentration dC mentioned in step S3 is calculated by the ratio of the characteristic absorption peak area of ​​the -NO2 group in the nitrate ester to the characteristic absorption peak area of ​​the -CH2 group in the internal reference peak.

8. The method for detecting the migration kinetics of energetic material components according to claim 6, characterized in that, The detection method further includes determining the content of the migrating component based on the characteristic absorption peak area of ​​the specific group corresponding to the migrating component and the characteristic absorption peak area of ​​the internal reference peak.

9. The method for detecting the migration kinetics of energetic material components according to claim 8, characterized in that, The content of the migrating component is calculated as follows: the relative concentration of the migrating component is obtained by selecting the ratio of the characteristic absorption peak area corresponding to the migrating component to the characteristic absorption peak area of ​​the internal reference peak, and the content of the migrating component is characterized by this relative concentration.

10. A method for detecting the migration kinetics of energetic material components according to any one of claims 1 to 9, characterized in that, The method is used for evaluating the adhesion performance of the solid rocket motor combustion chamber interface, rapid formula screening, and storage life prediction.